Terpenoid profiles of resin in the genus Dracaena are species specific - Vaníčková, Lucie; Pompeiano, Antonio; Maděra, Petr; Massad, Tara Joy; Vahalík, Petr (Phytochemistry, 2020)
Dragon's blood is the colloquial name for the red resin produced by tree species in the genus Dracaena (Asparagaceae), and the resin is directly involved in plant defensive mechanisms against pathogen and herbivore attack. It is also widely used in traditional folk medicine due to its antiviral, antimicrobial and antitumor activities. In the present work, a method using solid phase microextraction combined with two-dimensional gas chromatography with time-of-flight mass spectrometric detection was developed for the analysis of resin from five Dracaena species, namely Dracaena cinnabari Balf. f., D. serrulata Baker, D. ombet Heuglin ex Kotschy & Peyr., D. draco subsp. draco, and D. draco subsp. ajgal. Twenty terpenoid components in the resins of the five species were identified after comparative study of the volatile metabolite profiles. Monoterpenes were found to be species specific, and the observed differences might be further investigated as a possible means of identifying chemotaxonomic markers. In addition, for the first time, we describe the terpenoid volatile profiles of D. ombet and D. serrulata resins.
Keywords: PCA; fytonutrienty; Chromatography, Gas; rostlinné pryskyřice; mikroextrakce na pevné fázi; terpeny; druhová specificita; Terpenes; Resins, Plant; Species Specificity; SPME; Dracaena; Dracaena serrulata baker (Asparagaceae); hmotnostní spektrometrie; Dracaena draco (L.) L. (Asparagaceae); Dracaena cinnabari Balf.f. (Asparagaceae); GC×GC-MS; chromatografie plynová; Solid Phase Microextraction; Mass Spectrometry; Dracaena ombet heuglin ex kotschy & peyr. (Asparagaceae); Resin volatile profiles; Phytochemicals